DNA tetrahedron as nanoparticulated delivery system in combating diseases - Mandal, Ardhendu Kumar (Journal of Drug Delivery and Therapeutics, 2024)
Many diseases suffer from drug resistance and nucleic acid cargo delivery. To optimize pharmaceutics and to enhance their efficiency of cellular uptake, DNA nanomaterial tetrahedrons, owing to their precise control in size, shape, excellent biocompatibility and cellular permeability, reduced cytotoxicity, good stability, ease synthesis and multiple sites for targeting design, have attracted attention for targeting cargos delivery. Their nanostructural binding efficiency with many cargos depends on their electrostatic attractions among free electrons of phosphate oxygen, sugar and base nitrogen. Self-assembled DNA tetrahedrons (DTs) alone also can regulate cellular processes to some extent, especially, on migration, differentiation, proliferation and autophagy, and their modifications with the attachment of aptamers, peptides, nucleic acids, antibodies, different low-molecular-weight drugs and other components, make them a novel targeted delivery system as effective nanomedicine. This review demonstrates the current progress of DTs towards their synthesis, characterization, biomedical applications, biodistribution, elimination and toxicity as possible nanoparticulated delivery system. Keywords: Diseases; Drug resistance; DNA tetrahedron; nanoparticulated delivery system; Nanomedicine